Evaluating the Effects of the Olweus Bullying Prevention Program on Middle School Bullying - Kendrick, Michelle Marie (2015)
This project study addressed the problem of bullying, victimization, and the awareness of these activities at a public suburban middle school in Northwest Georgia. The study school implemented the Olweus Bullying Prevention Program (OBPP) in 2009, yet had not evaluated the program to identify whether or not it met its goals after 1 year of implementation. Using a quasiexperimental, goal-free program evaluation, the research questions explored whether or not the OBPP succeeded in reducing the student reported rates of bullying and victimization while also increasing awareness of such activities. A Mann Whitney U test was utilized for analysis due to violations of normality and homoscedasticity in the data. The quantitative sequence consisted of descriptive analyses of archived student data from the pre- and postimplementation (N = 346 and 137, respectively) Revised Olweus Bully/Victim Questionnaire (OBVQ) administration. Results indicated an increase, though not statistically significant, in student reporting of victimization and awareness and a statistically significant increase in rates of bullying. Results in the evaluation report supported continued OBPP implementation with anticipation that implementing more than 1 year should yield a decrease in student reported rates of bullying and victimization and increase in awareness of what constitutes these activities. The project study could lead to positive social change by increasing awareness of bullying in the learning community and reducing the number of reported incidents of bullying and victimization